Perbandingan Coping Stres Akademik Berdasarkan Jenis Kelamin pada Mahasiswa Tingkat Akhir Program Studi Bimbingan dan Konseling Universitas Sanata Dharma Yogyakarta - Leony Rantelili; Bernardinus Agus Arswimba (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to (1) determine the level of stress coping in final year male students of the Guidance and Counseling Study Program at Sanata Dharma University, Yogyakarta. (2) Knowing the level of stress coping in final year female students of the Guidance and Counseling Study Program at Sanata Dharma University, Yogyakarta. (3) Knowing the differences in levels of coping with academic stress between male and female students in the final year of the Guidance and Counseling Study Program at Sanata Dharma University, Yogyakarta. This type of research is comparative quantitative. The subjects in this research were final year students of the Guidance and Counseling study program at Sanata Dharma University, Yogyakarta, totaling 60 students from a total population of 77 students. The questionnaire was prepared based on aspects of coping stress according to Lazarus and Folkman (1984). The instrument's Alpha Chronbach reliability coefficient value is 0.947 with 51 valid items. The results of this study show that there is no difference in the level of academic stress coping in final year students of the Guidance and Counseling study program at Sanata Dharma University, Yogyakarta, seen from the significance value of 0.058 > α = 0.05. Students and female students have a high level of academic stress coping. The frequency of students' academic stress coping level was 23 (76.7%), while female students were 17 (56.7%).